ANALISIS PENGARUH DANA ALOKASI UMUM, BELANJA MODAL, DAN PRODUK DOMESTIK REGIONAL BRUTO TERHADAP PENDAPATAN ASLI DAERAH KABUPATEN/KOTA DI PROVINSI BALI - Putra, I Gede Rizky Mahendra; Algifari (LPPM STIE YKPN Yogyakarta, 2023)
This aims of this research is to find empirical evidence the impact of General Allocation Fund (DAU), Capital Expenditures (BM), and Gross Regional Domestic Product (GDP) on Original Revenue (PAD) in the province of Bali. This study uses data about PAD, DAU, BM, and PDRB 8 regencies and 1 city in the province of Bali in 2017-2021. The data obtained from Central Statistics Agency (BPS) report 2023. The research model that used to test the research hypothesis is the panel data regression model. The best model found was the random effects model. The results of this study found that DAU has a negative effect on PAD, while BM and GRDP have a positive influence on district/city PAD in the province of Bali.